Forward modeling magnetic fields of induced and remanent magnetization in the lithosphere using tesseroids. (November 2016) - Baykiev, Eldar; Ebbing, Jörg; Brönner, Marco; Fabian, Karl
Abstract: A newly developed software package to calculate the magnetic field in a spherical coordinate system near the Earth's surface and on satellite height is shown to produce reliable modeling results for global and regional applications. The discretization cells of the model are uniformly magnetized spherical prisms, so called tesseroids. The presented algorithm extends an existing code for gravity calculations by applying Poisson's relation to identify the magnetic potential with the sum over pseudogravity fields of tesseroids. By testing different lithosphere discretization grids it is possible to determine the optimal size of tesseroids for field calculations on satellite altitude within realistic measurement error bounds. Also the influence of the Earth's ellipticity upon the modeling result is estimated and global examples are studied. The new software calculates induced and remanent magnetic fields for models at global and regional scale. For regional models far-field effects are evaluated and discussed. This provides bounds for the minimal size of a regional model that is necessary to predict meaningful satellite total field anomalies over the corresponding area. Highlights: Tool for computation of the magnetic field of spherical prisms was developed. Appropriate width of spherical prisms for modeling is 1 or less degrees. Elliptic and spherical lithospheric models have approximately 2 nT difference. 15° Extension of a regional model is sufficient to avoid big edge effects.